Program Restoratif untuk Meningkatkan Keterampilan Sosial Anak Usia Dini di Daerah Tertinggal - Istnain Alfajri Husain; Erwin Eka Saputra; Chairan Zibar L. Parisu; La Sisi; Saqjuddin Saqjuddin (Jurnal Abdi Masyarakat dan Pemberdayaan Inovatif, 2025)
Early childhood social skills are an important foundation for children's success in socializing, learning, and building relationships in the future. In underdeveloped areas such as Mata Usu District, Bombana Regency, children experience limitations in developing social skills due to low access to quality education, lack of PAUD teacher training, and minimal parental participation. This community service aims to implement a restorative program as an educational approach to improving early childhood social skills. The implementation method includes identifying problems, training teachers and parents on the restorative approach, implementing role-playing and children's dialogue activities, and evaluating the results. The activity was carried out in one of the underdeveloped villages in Mata Usu District for two months. The results of the service showed a significant increase in children's social skills such as empathy, communication, and peaceful conflict resolution. Teachers and parents also showed increased understanding and involvement in guiding children with a restorative approach. This program shows that an empathy and communication-based approach is effective in areas with limited resources. Policy support and further training are needed so that this approach can be implemented sustainably in all PAUDs in Mata Usu District.